Analisis Kandungan Formalin Pada Ikan Asin Air Tawar Di Kabupaten Wajo - Inayah Inayah; Asmarani Asmarani (Direktorat Politeknik Kesehatan Makassar, 2024)
Tempe Lake which is located in Wajo Regency is the second largest lake in South Sulawesi Province. There are abundant fish produced which can be processed into salted fish products. Salted fish is made by preserving the fish by using salt. In the manufacturing process, people often use formalin-type food additives to make the storability can be longer. This research aims to analyse fomaldehyde content in wet saltwater fish, semi-dried salted fish, and dry saltwater fish in Tanjong Manik Market, Tempe District, Wajo Regency. The data were obtained through observation and laboratory examination using the test kit method. The number of samples in this research were 30 samples of salted fish using a purposive sampling technique. The results show that 90% of 30 samples contained formaldehyde for wet saltwater fish, 70% for semi-dried salted fish, and 90% for dry saltwater fish. Based on the results, it can be concluded that there is formalildehyde content in the freshwater salted fish in the samples examined. It is hoped that the public will know more about the characteristics of salted fish containing formalin. For the salted fish producers, it is hoped not to add food additives and maximize the drying process. The government is hoped to supervise and guide the producers on the use of formalin in food ingredients.